2006
DOI: 10.1002/hyp.6261
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the release of dissolved organic carbon and dissolved forms of nitrogen from a small upland headwater during autumn runoff events

Abstract: Abstract:We identify and assess the relative importance of the principal factors influencing the release of dissolved organic carbon (DOC) and dissolved forms of nitrogen (N) from a small upland headwater dominated by podzolic soils during a sequence of autumn runoff events. We achieve this by subjecting high-resolution hydrometeorological and hydrochemical data to an R-mode principal component factor analysis and a stepwise multivariate regression analysis. We find that the release of DOC and N is influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…Results indicated a significant influence of discharge on DOC concentrations, shown also in many other studies (Cooper et al, 2007;Grieve, 1994;Hope et al, 1994;Worrall et al, 2002). Cooper et al (2007) and Worrall et al (2002) described the importance of the amount of water flowing through soils and its transit time for flushing C out of soils.…”
Section: Dissolved Organic Carbon (Doc)supporting
confidence: 66%
See 4 more Smart Citations
“…Results indicated a significant influence of discharge on DOC concentrations, shown also in many other studies (Cooper et al, 2007;Grieve, 1994;Hope et al, 1994;Worrall et al, 2002). Cooper et al (2007) and Worrall et al (2002) described the importance of the amount of water flowing through soils and its transit time for flushing C out of soils.…”
Section: Dissolved Organic Carbon (Doc)supporting
confidence: 66%
“…These studies reported increasing concentrations in Scottish landscapes from June to November and from May to June, respectively. The early autumn is considered to be the time of maximum DOC export (Cooper et al, 2007;Grieve, 1984;Worrall et al, 2004). The rising trend can result from increasing soil temperature and moisture which are driving factors for decomposition.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%
See 3 more Smart Citations